Development of Multi-Actuated Ground Vehicles: Educational aspects. Issue 9 (2018) - Ivanov, Valentin; Augsburg, Klaus; Blundell, Mike; Nijs, Wouter De; Desmet, Wim; Ferrara, Antonella; Kanarachos, Stratis; Kiele-Dunsche, Mathias; Klomp, Matthijs; Metzner, Steffen; Naets, Frank; Nedoma, Pavel; et al.
Abstract: This paper introduces the setup of the European network ITEAM aimed at the training of early-stage researchers (ESR) in the field of multi-actuated ground vehicles (MAGV). A network concept includes three main domains, where fifteen interconnected individual research projects are allocated: MAGV Integration, Green MAGV, and MAGV Driving Environment. All the projects are being carried out within the framework of continuous interdisciplinary training. The paper is focused on emerging research and technological trends, which are under elaboration in ITEAM projects, and the role of practice-oriented educational methods for their realization.